Evidence-based patient choice. Issue 2 (1st April 1999) - Hope, Tony
Abstract : Evidence-based medicine and patientcentred care are natural bedfellows. Muir Gray coined the term "evidencebased patient choice" (1); Entwistle and colleagues (2) have written about evidence-informed patient choice. Both of these modern movements have developed as a critical response to what is perceived to be the excessive authority given in traditional medicine to doctors and other health professionals. Evidence-based medicine emphasises the point that it is not the authority of the doctor that justifies a particular clinical intervention but the evidence for that intervention's effectiveness.